2012
DOI: 10.1590/s1516-14392012005000010
|View full text |Cite
|
Sign up to set email alerts
|

Prediction total specific pore volume of geopolymers produced from waste ashes by fuzzy logic

Abstract: In the present work, total specific pore volume of inorganic polymers (geopolymers) made from seeded fly ash and rice husk bark ash has been predicted by fuzzy logic. Different specimens, made from a mixture of fly ash and rice husk bark ash in fine and coarse form together with alkali activator made of water glass and NaOH solution, were subjected to porosimetry tests at 7 and 28 days of curing. The curing regime was different: one set of the specimens were cured at room temperature until reaching to 7 and 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Steel fibers were added to the mixtures just before casting in molds. Specimens were then preserved for 24 h at room temperature because this precuring time has been found to be beneficial to strength development [18] Precuring time before application of heat induces significant dissolution of silica and alumina from slag mixture and formation of a continuous matrix phase, this increasing homogeneity of the geopolymeric material [18,19]. After the precuring process, the samples cured in oven at 70 ºC for 6h.…”
Section: Methodsmentioning
confidence: 99%
“…Steel fibers were added to the mixtures just before casting in molds. Specimens were then preserved for 24 h at room temperature because this precuring time has been found to be beneficial to strength development [18] Precuring time before application of heat induces significant dissolution of silica and alumina from slag mixture and formation of a continuous matrix phase, this increasing homogeneity of the geopolymeric material [18,19]. After the precuring process, the samples cured in oven at 70 ºC for 6h.…”
Section: Methodsmentioning
confidence: 99%
“…These authors observed the trend of strong degradation of the PET during processing due the presence of organic modifier, a slight increase in crystallinity and a slight change on Young's modulus for all clay contents below 10 wt%. 10,11,12 . The purpose of this study was to develop composites containing high amounts of pulverized geopolymer concrete waste, treated and untreated with oleic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Metakaolinite, present in metakaolin (MK), is the main source of aluminum in the geopolymer. The geopolymerization occurs due to the destruction and recombination of the aluminosilicate chains of the disorganized kaolinite (metakaolinite) from the action of OH -ions and alkalis, specifically in the aluminum-containing sites 5 . Therefore, any impediment to this reaction, such as the entrapment or insufficiency of ions or the substitution by impurity atoms in the original kaolinite structure, can modify the kinetics of the geopolymerization and even hinder obtaining the necessary structural properties in the geopolymer 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The geopolymerization occurs due to the destruction and recombination of the aluminosilicate chains of the disorganized kaolinite (metakaolinite) from the action of OH -ions and alkalis, specifically in the aluminum-containing sites 5 . Therefore, any impediment to this reaction, such as the entrapment or insufficiency of ions or the substitution by impurity atoms in the original kaolinite structure, can modify the kinetics of the geopolymerization and even hinder obtaining the necessary structural properties in the geopolymer 5 . In the Brazilian Civil Construction market, there has been a recent increase in the supply of the phyllite ore, integrating ready-mixed sand mortars and additives for use in coating mortars and laying of red ceramic masonry.…”
Section: Introductionmentioning
confidence: 99%